2019
DOI: 10.1155/2019/7850392
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Levels in Gingival Crevicular Fluid, Saliva, and Serum of Chronic Periodontitis Patients

Abstract: Chronic periodontitis (CP) is an infection that affects the teeth supporting structure. Macrophage migration inhibitory factor (MIF) is an important effector cytokine of the innate immune system. Due to its functional characteristics, MIF may be involved in the immunopathology of CP. The aim of the present study was to evaluate MIF levels in gingival crevicular fluid (GCF), saliva, and serum of CP patients. A cross-sectional study was conducted on 60 subjects divided into two groups: subjects with CP (n= 30) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…Plastin-2 (LCP1) regulates leukocyte adhesion to integrin and has been described among salivary proteins associated with periodontitis in patients with type 2 diabetes mellitus [ 24 ]. Finally, macrophage migration inhibitory factor (MIF), another important effector cytokine of the innate immune system, has been also associated with the disease severity in chronic periodontitis [ 25 ]. Noteworthy, none of our patients presented a clinically evident periodontitis thus we hypothesized that salivary EVs cargo may represent a useful source of early biomarkers able to reflect initial alterations of the gingival crevicular fluid and subclinical abnormalities of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Plastin-2 (LCP1) regulates leukocyte adhesion to integrin and has been described among salivary proteins associated with periodontitis in patients with type 2 diabetes mellitus [ 24 ]. Finally, macrophage migration inhibitory factor (MIF), another important effector cytokine of the innate immune system, has been also associated with the disease severity in chronic periodontitis [ 25 ]. Noteworthy, none of our patients presented a clinically evident periodontitis thus we hypothesized that salivary EVs cargo may represent a useful source of early biomarkers able to reflect initial alterations of the gingival crevicular fluid and subclinical abnormalities of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Deserves special attention the idea of [6,16] bacterial contamination as a factor of the development of experimental periodontitis, which was proposed in 2015 [14]. There is proposed the concept of an increase in the role of bacterial contamination in patients with periodontitis against the background of a decrease in the expression of antimicrobial peptides in the epithelium of oral cavity, which can further lead to invasion of initiation of chronic systemic inflammation [17,18]. Our study of the spectrum of cytokines showed that the concentration of pro-inflammatory cytokines significantly increases at the 60th and 90th day of the experiment (concentration of IL-1β and TNF-α and anti-inflammatory IL-10 significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gene inactivation of MIF receptor (CD74) or the use of MIF agonist ISO-1 resulted in a significant reduction in the proliferation of gastric cancer cells [ 84 ]. Therefore, the higher concentrations of serum and salivary MIF observed in PD might stimulate the proliferation, metastasis and invasion, of oral cancer cells into other tissues [ 85 ].…”
Section: Oscc Immune Permissive Environment Induced By Periodontal Diseasementioning
confidence: 99%